Spatial Analysis in Work Comfort and Performance Optimization of the Financial Planning Section of the Medan City Education Office - Nadia Evira; Marliyah Marliyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Office layout is an important aspect in supporting employee performance. The arrangement of an office describes how employees in the office work in their daily lives. Every employee in the office certainly needs space to work. Irregular office layout will make employees or other office occupants feel uncomfortable in doing their jobs. This discomfort will affect the optimization of the work of employees in an organization. Therefore, the right office layout will make it easier for employees to work so that their work productivity can be optimal and show good results. This study used qualitative research methods. This study uses primary data obtained directly through observation, interviews and documentation.